2006
DOI: 10.1111/j.1746-1561.2006.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Smoking, Drinking, and Marijuana Use Between Students Present or Absent on the Day of a School-Based Survey

Abstract: The aim of this population-based survey was to compare the prevalence of selected risk behaviors between students present or absent on the day of a school-based survey. The study population was a representative sample of all students of secondary schools in the Seychelles (Indian Ocean). Students absent on the day of the survey were traced and requested to complete the same self-administered questionnaire as did present students. Self-reported consumption of cigarettes, alcohol, and marijuana were measured. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 27 publications
1
42
0
1
Order By: Relevance
“…Although the response rate was high and the data were weighted to help account for nonresponse, the findings are nevertheless subject to sample bias. In addition, the findings likely reflect some underreporting for substance use as is common in survey research [10]. The cross-sectional nature of the data does not allow for causal inferences regarding the association between bidi and hookah use and the correlates examined.…”
Section: Discussionmentioning
confidence: 76%
“…Although the response rate was high and the data were weighted to help account for nonresponse, the findings are nevertheless subject to sample bias. In addition, the findings likely reflect some underreporting for substance use as is common in survey research [10]. The cross-sectional nature of the data does not allow for causal inferences regarding the association between bidi and hookah use and the correlates examined.…”
Section: Discussionmentioning
confidence: 76%
“…Missing classes/school evasion is an important risk marker, being generally associated with an unstable family environment. Other studies point out that students who were absent from school are more involved with the use of substances than the ones who attended classes 25 . Family relationships and cohesions, as well as participating in activities together with family members, have a protective effect on the prevention against the use of alcohol and other drugs 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the report of the use of substances may reflect the perception of such use, and not the real situation, which may end up reflecting more experimentation than regular use. Besides, the study was conducted with students with good school attendance, and the real prevalence of the use of substances among adolescents may have been underestimated, since students who miss school tend to present higher prevalence of risk behaviors than the one who do not miss classes (on a test day) 25 . Besides, this is a cross-sectional study, and the observed associations do not necessarily have a cause-effect relationship; this would be better observed in longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study is based on a cross-sectional survey of secondary school students; therefore, the findings cannot be generalized to all New Zealand adolescents. Young people who do not attend mainstream schools or who are absent from school are not as healthy as their peers who are well engaged in mainstream schooling (Bovet et al, 2006;Clark et al, 2010;Denny et al, 2004). Self-harm 1785(20.3, 18.9-21.8) 2015(24.0, 22.7-25.4) --Males 725 (15.5, 14.1-16.8) 681 (17.9) (16.6-19.2) --Females 1060(26.0, 24.4-27.6) 1332(29.1, 27.4-30.8) --≤15 1225(21.4, 19.8-23.1) 1315 Values are n (%, 95% CI) or adjusted odds ratio (95% CI).…”
Section: Strengths and Limitationsmentioning
confidence: 99%